The Effect of Giving Commercial Agar Chewing Materials on the Yield and Organoleptic Quality of Chicken Meatballs - Anita Mustika Ibrahim; Harapin Hafid (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
Increasing the elasticity of meatballs can be done by adding a thickening agent in the manufacture of meatballs including chicken meatballs with natural or artificial ingredients. The research aims to produce processed meat products with better quality and to evaluate consumer preference for chicken meatballs with flour as a thickener so that they are commercially available through yield and organoleptic tests. This study used a completely randomized design with a 3x3 factorial pattern with 4 replications for the yield test and 10 repetitions for the meatball organoleptic test. The first factor is the thickening agent of agar flour nutrijel, swallow globe, and rajawali. While the second factor is the level of the thickening agent 3%, 4%, and 5%. Research variables include yield value and organoleptic quality (color, aroma, texture, and taste). The results showed that the addition of flour thickening agent had a significant effect (P<0.05) on the yield value, and had an insignificant effect (P>0.05) on the organoleptic test of chicken meatballs. Where the best type and level of addition of agar flour on the yield value is found in the type of flour swallow globe agar with a level of 5%.